A forum-based organizational memory as organizational learning support - Leblanc, A.; Abel, M.-H. (Journal of Digital Information Management, 2008)
Information and Communication Technologies have transformed the way people work and have a growing impact on long life learning. Organizational Learning is an increasingly important area of research that concerns the way organizations learn and thus augment their competitive advantage, innovativeness, and effectiveness. Within the project MEMORAe2.0, we are interested by the capitalization of knowledge in the context of an organization and by organizational learning. We developed the EMEMORAe2.0 environment which is based on the concept of learning organizational memory. In this paper, we present the organizational learning approach; we stress the role of an organizational memory in this approach; we define the concept of learning organizational memory; and we specify the use of a forum concept in such a context. Then we present the approach MEMORAe, the environment E-MEMORAe2.0 we developed and its evaluation.
Keywords: Community of practice; Forum; Learning organizational memory; Ontology; Organizational learning